Kepemimpinan Profetik di Era 4.0 - Zuhri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Abstract The study of the prophetic leadership, certainly can not escape from the figure of the Prophet Muhammad SAW as the only most perfect figure ever sent by Allah to the face of this earth which is even termed the good Suri of example (Uswatun Hashanah). With a library research approach, the results explained that the concept of prophetic leadership in Islam is built on the teachings of the Qur'an, Sunnah of Rasulullah Saw and Khulafa ar-Rasyidin, so that the leadership is positioned as a divine contract, where the responsibility of the leadership is not only limited to social responsibility but also religious-spiritual. The concept of this leadership was built upon the study of the Qur'an, Sunnah, Khulafa ar-Rasyidin, and human behavior as servants and caliphs on Earth. The prophetic leadership of Islam remains absolute and has not been replaced by any theories, because this leadership theory since its emergence (Lauh al Mahfuzd in the context of the Qur'an and the prophetic treatise of Muhammad Saw in the context of Sunnah) has been guaranteed as the most perfect leadership model of all time where there will be no